Effect of Early Warning Score on Length of Stay and Mortality of Non-Surgical Patients in the Intensive Care Room at Dr. Moewardi Hospital Surakarta - Luthfiana Nadhiifa Khoirunnisa; Arifin Arifin; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: One of the efforts to improve the quality of life and patient safety in hospitals is the use of the Early Warning Score (EWS). The purpose of this study was to analyze the effect of EWS on the length of stay and mortality of non-surgical patients in the intensive care unit of Dr. Moewardi Hospital Surakarta.Subjects and Method: This study is an observational study conducted using a prospective cohort study. A purposive sampling study conducted on June 10 - July 10 was carried out by taking a sample of 120 non-surgical patients in the ICU of Dr. Moewardi Hopital, Surakarta with inclusion and exclusion criteria. This study chose the early warning score as the independent variable and length of stay and mortality as the dependent variable. The method of collecting data on EWS, length of stay, and mortality was using an observation sheet filled out by the researcher. This study assessed differences in baseline characteristics and outcomes using the Chi-Square test and one-way analysis of variance (ANOVA).Results: There is a statistically significant effect of EWS on length of stay (p = 0.024). EWS also has a statistically significant effect on mortality p<0.001.Conclusion: There is an effect of EWS on the length of stay and mortality of non-surgical patients.Keywords: EWS, length of stay, mortality, non-surgical patients, intensive careCorrespondence: Luthfiana Nadhiifa Khoirunnisa. Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: luthfiana@student.uns.ac.id. Mobile: +62 82111170000.Indonesian Journal of Medicine (2023), 08(03): 310-316https://doi.org/10.26911/theijmed.2023.08.03.08